Creating opportunities for interprofessional communitybased education for the undergraduate dental therapy degree in the School of Health Sciences University of KwaZuluNatal South Africa: Academics’ perspectives - I Moodley; S Singh (South African Medical Association, 2018)
Background. Interprofessional education (IPE) provides opportunities for students from two or more health profession disciplines to learn with, from and about each other, to foster collaborative practice in the future, when health professionals are expected to work in healthcare teams. While there are many documented examples of IPE among student health professionals in the literature, dental therapy student participation in IPE has been excluded.Objectives. To explore the opportunities for dental therapy students to participate in collaborative interprofessional, community-based initiatives by engaging with academics in the School of Health Sciences at the University of KwaZulu-Natal.Methods. This qualitative study used audiotaped interviews and focus-group discussions with a purposively selected sample of academics, and the results were thematically analysed.Results. The academics noted several opportunities for dental therapy students to participate in interprofessional, community-based education on various platforms, including school, primary healthcare and other community-based settings. Barriers that may hamper implementation include finding a common time for IPE in the uniprofessional curricula, matching student numbers and lack of staff support.Conclusion. The study findings revealed that opportunities exist for community-based IPE interventions for dental therapy students. However, both the creation and implementation of interprofessional interventions require individual lecturers to act as drivers across all disciplines.